776. The prevalence of HIV among hospitalized persons with acute febrile illness in rural Uganda, August 2019-June 2020. (31st December 2020) - Blair, Paul W; Kobba, Kenneth; Robinson, Matthew; Candia, Emmanuel; Aniku, Gilbert; Matovu, Alphonsus; Kakooza, Francis; Walwema, Richard; Lamorde, Mohammed; Manabe, Yukari C
Abstract: Background: In Uganda, in the early PEPFAR era, HIV coinfections were responsible for most hospitalizations with febrile illness (as high as 85% in 2006). Currently, national guidelines recommend universal antiretroviral therapy ideally before the development of AIDS. We evaluated the prevalence of HIV among patients admitted to two regional referral hospitals with febrile illness in the era of 'Treat All.' Methods: Participants admitted to two regional referral hospitals in Uganda were enrolled at emergency departments or medical wards. Participants uniformly received blood cultures, malaria (rapid diagnostic test), and tuberculosis (Xpert MTB/RIF Ultra), hepatitis A IgM, hepatitis B sAg, and HIV fourth generation testing were performed. Among participants with HIV, cryptococcal antigen testing and urine lipoarabinomannan (LAM) were performed. Results: From August 2019-June 2020, 95 participants (58% female) with an average age of 36.2 (SD 14.1) years, presented from 11 districts in Uganda. Participants presented at facilities 4.9 days (SD: 2.5) after onset of symptoms. Additionally, 16.1% of participants had a qSOFA (quick Sepsis Related Organ Failure Assessment) severity score of 2 or greater. By 28 days, 11.0% (n=7) died and 10.8% were lost to follow-up. On admission, 25.3% (n=24) of participants had a known history of HIV, the majority (87.5%) were on ART on hospital presentation. Of the 9.5% (n=9) who were newly diagnosed with HIV during the admission 6 were started on ART during hospitalization or within a month after hospitalization. Microbiologic and rapid diagnostic test results included positive results for tuberculosis (2.1%, 2/95 PCR; 3/16 urine LAM), malaria (29.5%, 28/95), cryptococcal antigen positive (12.5%; 2/15), hepatitis A (1.1%, 1/95), and hepatitis B (5.3%, 5/95). Blood cultures were positive in 11.1% of patients (10/90) with S. pneumoniae being most common isolate (N=4). Conclusion: In the universal ART era, the proportion of hospitalized febrile patients with HIV has decreased. Overall, 10% have newly diagnosed infection emphasizing the importance of continuing to test all hospitalized febrile patients. Diagnostic evaluations are needed to assess the burden of other causes of febrile illness in order to reprioritize potential differential diagnoses. Disclosures: All Authors : No reported disclosures